A block all-carbon-carbon connected proton exchange membrane and its preparation method and application

By designing a proton exchange membrane with block full carbon carbon connection, the problem of difficult balance between existing membranes between high IEC and mechanical stability is solved, the resistance to radicals and mechanical strength is improved, and the efficient proton exchange performance is achieved.

CN118562175BActive Publication Date: 2025-04-01FOSHAN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410654192.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-04-01
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

The existing proton exchange membranes are difficult to balance between high IEC and mechanical stability, which can easily lead to membrane expansion and contraction and reduce mechanical strength; at the same time, the stability of the anti-radical resistance is insufficient, and it is easy to be attacked by free radicals and lead to degradation.

Method used

The proton exchange membrane is designed with block full carbon carbon connection structure, through the poly(aryl-alkylene) backbone without ether bonds, avoid the heteroatom electron donation effect, improve the stability of radical resistance, and increase the sulfonic acid group introduction site through the polybenzene ring structure to increase IEC.

Benefits of technology

It achieves high IEC, high chemical stability, low water absorption swelling rate and high mechanical strength, improves the overall performance of the proton exchange membrane and is suitable for the electrolyte of the proton exchange membrane fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118562175B_ABST
    Figure CN118562175B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of fuel cells, and specifically discloses a proton exchange membrane of block full carbon carbon connection and its preparation method and application, and utilizes 1 3 kinds of components of formula 1A structure and 1 3 kinds of components of formula 2A structure to obtain the first intermediate polymer by super acid F C reaction under catalyst, and the first intermediate polymer obtains the sulfonated polymer after sulfonation reaction, and then forms a film to obtain the proton exchange membrane of block full carbon carbon connection. The proton exchange membrane prepared by the present invention includes a poly (aryl alkylene) main chain without ether bond; the main chain does not contain heteroatoms such as sulfur, ether, and oxygen, and avoids the electron donation effect of these heteroatoms to produce unstable electron-rich sites on the aromatic group, so that hydroxyl radicals are not easy to attack the sulfonated phenylene polymer, thereby improving its free radical resistance stability, and more sites for introducing sulfonic acid groups can be provided while polyphenyl rings, which is conducive to improving IEC; high chemical stability, low water absorption swelling rate, and high mechanical strength are simultaneously possessed; it can be used as an electrolyte of a proton exchange membrane fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fuel cells, in particular to a segmented all-carbon-carbon-connected proton exchange membrane and a preparation method and application thereof. Background Art

[0002] The working environment of PEM fuel cells (PEMFC) experiences different humidity conditions. Under high humidity, the membrane absorbs more water and expands, while under low humidity conditions, it loses water and shrinks. The water absorption and dehydration process caused by this humidity change will cause the membrane to expand and shrink repeatedly. If the expansion caused by water absorption is too large, the frequent volume changes will weaken the mechanical strength of the membrane and may eventually cause the membrane material to break. Therefore, it is crucial to balance IEC and mechanical stability when designing and selecting PEM materials.

[0003] Chinese patent application number CN202211262418.0 discloses a proton exchange membrane, which includes at least one of a polymer P1 containing a structural unit shown in formula (1) and a polymer P2 containing a structural unit shown in formula (2). The proton exchange membrane has high phosphate adsorption, high proton conductivity, high mechanical stability and antioxidant stability. Patent application number CN202211262417.6 discloses a proton exchange membrane, which belongs to the field of fuel cell technology. The proton exchange membrane provided in this application includes at least one of a polymer I containing a structural unit shown in formula (1), a polymer II containing a structural unit shown in formula (2), a polymer III containing a structural unit shown in formula (3), and a polymer IV containing a structural unit shown in formula (4). The proton exchange membrane disclosed in this application has high proton conductivity, high mechanical stability, high water retention capacity and high antioxidant properties.

[0004] However, the above-mentioned proton exchange membrane has the following technical problems:

[0005] 1. Sulfonated polyaryl polymers with high IEC have high proton conductivity, but the membrane is hydrophilic and swells greatly; although polymers with low IEC can have better water resistance, their proton conductivity is low, which has an adverse effect on battery efficiency.

[0006] 1. Anti-free radical stability problem: The operation of water electrolysis fuel cells will generate a large number of HOO· and HO· free radicals. These free radicals react with polymer aromatic substances to cause polymer degradation. The polymer structure connected by heteroatoms is easily degraded under the attack of free radicals.

[0007] Therefore, it is necessary to develop a block-type all-carbon-carbon connected proton exchange membrane. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a block all-carbon-carbon connected proton exchange membrane and a preparation method and application thereof.

[0009] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0010] One of the purposes of the present invention is to provide a method for preparing a block all-carbon-carbon connected proton exchange membrane, comprising the following steps:

[0011] S1. Dissolve 1 to 3 components of the structure of Formula 1A and 1 to 3 components of the structure of Formula 2A in an organic solvent, cool to 0°C with an ice bath, dropwise add a super acid catalyst, and perform polymerization reaction under ice bath conditions for 2h-12d. After the reaction is completed, sink into ice water to obtain a white solid, repeatedly rinse with deionized water for multiple times, and then vacuum dry to obtain an intermediate polymer; wherein the structural formulas of Formula 1A and Formula 2A are:

[0012]

[0013] In Formula 1A, each R 100 are independently one of a nitrogen-containing heterocyclic group, an alkyl group, an alkenyl group, an alkynyl group, or a substituent having Formula 1B:

[0014]

[0015] The nitrogen-containing heterocyclic group is a substituted pyrrole, pyrroline, pyrazole, pyrazoline, imidazole, imidazoline, triazole, pyridine, triazine, pyrazine, pyridazine, pyrimidine, azepine, quinoline, piperidine, pyrrolidine, pyrazolidine, imidazolidine, azepane, isoxazole, isoxazoline, oxazole, oxazoline, oxadiazole, oxatriazole, dioxazole, oxazine, oxadiazine, isoxazolidine, morpholine, thiazole, isothiazole, oxathiazole, oxathiazine or caprolactam, wherein each substituent is independently sulfonic acid, alkyl, alkenyl, alkynyl, aryl or aralkyl, and the alkyl, alkenyl, alkynyl or aryl is substituted with a halide; R 90 , R 110 , R 120 , R 130 and R 140 Each is independently one of a sulfonic acid group, hydrogen, a halide, an alkyl group, an alkenyl group, an alkynyl group or an aryl group, and the alkyl group, the alkenyl group, the alkynyl group or the aryl group is substituted with a halide; illustratively, the representative monomers of Formula 1A include but are not limited to the following trifluoroketone monomers:

[0016]

[0017] Trifluoroacetone, trifluorobutanone, trifluoropentanone, trifluorohexanone, trifluoroheptanone, trifluorooctanone, etc.; trifluoroacetophenone, 2-trifluoromethyl-trifluoroacetophenone, 3-trifluoromethyl-trifluoroacetophenone, 4-trifluoromethyl-trifluoroacetophenone, 3,5-bis(trifluoromethyl)-trifluoroacetophenone, etc.;

[0018] In Formula 2A, n represents an integer between 0 and 5; R 10 , R 20 , R 30 , R 40 , R 50 , R 60 , R 70 and R 80 are each independently one of sulfonic acid, hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is substituted with halide, wherein R 30 and R 60 Connecting a halide or alkyl-substituted five-membered ring; illustratively, representative monomers of Formula 2A include but are not limited to: biphenyl, terphenyl, m-terphenyl, quaterphenyl, pentphenyl, 1-trifluoromethyl-3,5-diphenylbenzene, etc.;

[0019] S2. In an inert gas atmosphere, an anhydrous organic solvent is added to the intermediate polymer, and the polymer is stirred until dissolved, and then a sulfonating agent is added dropwise to carry out a sulfonation reaction for 1 to 14 days; after the reaction is completed, the mixture is rotary evaporated to remove excess solvent; the obtained solid is dissolved in the organic solvent, and the mixture is poured into an aqueous solution of NaOH, and the precipitated solid is washed with deionized water for several times, and then washed once with an organic solvent and filtered to obtain a sulfonated polymer;

[0020] S3. Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. Vacuum dry the obtained polymer, dissolve it in a polar solvent and centrifuge it, cast it on a substrate or a porous substrate, dry it at 60-100°C for 5-24 hours to form a membrane, and then vacuum dry it at 80-150°C for 5-24 hours to obtain a proton exchange membrane with a thickness of 10-100 μm.

[0021] In this embodiment, an enhanced proton exchange membrane can be made by casting on a porous substrate. Such an enhanced proton exchange membrane can be prepared by methods including but not limited to the following: wetting a porous substrate in a liquid to form a wetted porous substrate; dissolving a sulfonated polymer in a solvent to form a uniform solution; applying the solution to the wetted porous substrate to form the enhanced membrane; drying the enhanced membrane; any known membrane forming technique, such as casting, spraying, impregnation or scraping to the wetted substrate. If necessary, the enhanced membrane can be impregnated with the sulfonated polymer multiple times by wetting the enhanced membrane again and repeating the dissolving, casting and drying steps. The liquid used to wet the porous substrate may be a low boiling point solvent, such as a lower alcohol (e.g., methanol, ethanol, propanol, isopropanol) or water. Preferably, the liquid is anhydrous ethanol. The thickness of the porous substrate may be 1 μm to 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100 μm. Preferably, the thickness of the porous substrate is 5 to 30 μm, or 7 to 20 μm.

[0022] Furthermore, the organic solvent is one or more combinations of dichloromethane, chloroform, dichloroethane, trifluoroacetic acid, trifluoromethanesulfonic acid, chloroform, 1,1,2,2-tetrachloroethane, and dimethylacetamide.

[0023] Furthermore, the super acid catalyst is one or more combinations of trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, heptafluoro-1-propanesulfonic acid, trifluoroacetic acid, perfluoropropionic acid, and heptafluorobutyric acid.

[0024] Furthermore, the sulfonating agent is one or more combinations of chlorosulfonic acid, acetylsulfonic acid, concentrated sulfuric acid, sulfur trioxide, and trimethylsilylchlorosulfonic acid.

[0025] Furthermore, the inert gas is argon.

[0026] Furthermore, in step S1, the vacuum drying temperature is 80° C. and the time is 12 h.

[0027] Furthermore, the polar solvent is one or more combinations of N-methylpyrrolidone, dimethylacetamide, dimethyl sulfoxide, and dimethylacetamide.

[0028] Furthermore, the substrate is one of stainless steel plate, glass plate, polyethylene terephthalate plastic PET plate, polypropylene PP plate, and polyester film; the porous substrate is one of polyphenylene sulfide PPS perforated plate, polyetheretherketone PEEK perforated plate, polyethylene terephthalate plastic PET perforated plate, polytetrafluoroethylene perforated plate, polyvinylidene fluoride perforated plate, stainless steel plate perforated plate, polypropylene PP perforated plate, polyethylene PE perforated plate, and glass fiber cloth.

[0029] The second object of the present invention is to provide a block all-carbon-carbon connected proton exchange membrane prepared by the above method.

[0030] The third object of the present invention is to provide a block all-carbon-carbon connected proton exchange membrane for use in the preparation of proton exchange membrane fuel cells.

[0031] Compared with the prior art, the proton exchange membrane prepared by the present invention comprises a poly(aryl-alkylene) main chain without an ether bond; the main chain does not contain heteroatoms such as sulfur, ether and oxygen, thereby avoiding the electron-donating effect of these heteroatoms to produce unstable electron-rich sites on the aromatic group, making it difficult for hydroxyl radicals to attack the sulfonated phenylene polymer, thereby improving its free radical resistance stability; multiple benzene rings can provide more sites for introducing sulfonic acid groups, which is beneficial to improving IEC; the present invention also has high chemical stability, low water absorption and swelling rate, and high mechanical strength; and the present invention can be used as an electrolyte for a proton exchange membrane fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the mechanical properties diagram of proton exchange membrane sample 5.

[0033] Figure 2 This is the polarization curve of proton exchange membrane sample 5.

[0034] Figure 3 This is a stability test diagram of proton exchange membrane sample 5.

[0035] Figure 4 These are weight loss graphs of proton exchange membrane sample 2, proton exchange membrane sample 5, and proton exchange membrane sample 8. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0037] In the following examples, block all-carbon-carbon connected proton exchange membranes were prepared using representative monomers of Formula 1A and Formula 2A. The raw materials and reagents used were commercially available or prepared using conventional methods in the art unless otherwise specified.

[0038] Example 1

[0039] Step 1: Dissolve trifluorobutanone (12.6 g, 0.1 mol), p-terphenyl (11.5 g, 0.05 mol), and biphenyl (7.8 g, 0.05 mol) in 60 ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 ml, 0.9 mol). After the dropwise addition, polymerize for 12 hours in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it several times with deionized water, and then vacuum dry it at 80°C for 12 hours to obtain an intermediate polymer.

[0040] Step 2: Add the above intermediate polymer (0.9 g, 3.000 mmol) to a flask, and pass argon gas into it for 30 min; add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise, and react under this condition for 12 h (Note: the key is anhydrous reaction). After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water, washed once with DCM and filtered to finally obtain the target sulfonated polymer. The synthesis equation is as follows:

[0041]

[0042] Step 3: The sulfonated polymer is washed with distilled water and filtered to obtain a light yellow powdery polymer. The obtained polymer is vacuum dried at 80°C for 24 hours, dissolved in a polar solvent NMP and centrifuged, cast on a glass plate or a stainless steel plate, and dried at 60°C for 5 hours under infrared to form a film, and then vacuum dried at 80°C for 5 hours to obtain a proton exchange membrane sample 1 with a thickness of 50 μm.

[0043] Example 2

[0044] Step 1: Dissolve trifluorobutanone (12.6 g, 0.1 mol), m-terphenyl (11.5 g, 0.05 mol), and biphenyl (7.8 g, 0.05 mol) in 60 ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 ml, 0.9 mol). After the dropwise addition, polymerize for 12 hours in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it several times with deionized water, and then vacuum dry it at 80°C for 12 hours to obtain an intermediate polymer.

[0045] Step 2: Add the above intermediate polymer (0.9 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise to react for 24 h. After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water, washed once with DCM and filtered to obtain the target sulfonated polymer. The synthesis equation is as follows:

[0046]

[0047] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying the obtained polymer at 80°C for 24 hours, dissolve it in a polar solvent DMF and centrifuge it, cast it on a glass plate or a stainless steel plate, dry it at 60°C for 5 hours under infrared light to form a film, and then vacuum dry it at 80°C for 5 hours to obtain a proton exchange membrane sample 2 with a thickness of 50 μm.

[0048] Example 3

[0049] Step 1: Dissolve trifluorobutanone (12.6 g, 0.1 mol), m-terphenyl (11.5 g, 0.05 mol), and p-biphenyl (11.5 g, 0.05 mol) in 60 ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 ml, 0.9 mol). After the dropwise addition, polymerize for 12 hours in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it several times with deionized water, and then vacuum dry it at 80°C for 12 hours to obtain an intermediate polymer.

[0050] Step 2: Add the above intermediate polymer (0.9 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise to react for 36 h. After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water, washed once with DCM and filtered to obtain the target sulfonated polymer. The synthesis equation is as follows:

[0051]

[0052] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying the obtained polymer at 80°C for 24 hours, dissolve it in a polar solvent DMSO and centrifuge it, cast it on a glass plate or a stainless steel plate, dry it at 60°C for 5 hours under infrared light to form a film, and then vacuum dry it at 80°C for 5 hours to obtain a proton exchange membrane sample 3 with a thickness of 50 μm.

[0053] Example 4

[0054] Step 1: Dissolve 1-(3,5-bis(trifluoromethyl)phenyl)-2,2,2-trifluoroethanone (31g, 0.1mol), p-terphenyl (11.5g, 0.05mol), and biphenyl (7.8g, 0.05mol) in 60ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6ml, 0.9mol). After the dropwise addition, polymerize for 12h in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it repeatedly with deionized water several times, and then vacuum dry it at 80°C for 12h to obtain an intermediate polymer.

[0055] Step 2: Add the above intermediate polymer (1.2 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise, and react under this condition for 7 days (Note: the key is anhydrous reaction). After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water, washed once with DCM and filtered to finally obtain the target sulfonated polymer. The synthesis equation is as follows:

[0056]

[0057] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying the obtained polymer at 80°C for 24 hours, dissolve it in a polar solvent DMAc and centrifuge it, cast it on a glass plate or a stainless steel plate, dry it at 60°C for 5 hours under infrared light to form a film, and then vacuum dry it at 80°C for 5 hours to obtain a proton exchange membrane sample 4 with a thickness of 50 μm.

[0058] Example 5

[0059] Step 1: Dissolve 1-(3,5-bis(trifluoromethyl)phenyl)-2,2,2-trifluoroethanone (31g, 0.1mol), m-terphenyl (11.5g, 0.05mol), and biphenyl (7.8g, 0.05mol) in 60ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6ml, 0.9mol). After the dropwise addition, polymerize for 12h in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it repeatedly with deionized water several times, and then vacuum dry it at 80°C for 12h to obtain an intermediate polymer.

[0060] Step 2: Add the above intermediate polymer (1.2 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise to react for 12 h. After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water, washed once with DCM and filtered to obtain the target sulfonated polymer. The synthesis equation is as follows:

[0061]

[0062] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying the obtained polymer at 80°C for 24 hours, dissolve it in a polar solvent NMP and centrifuge it, cast it on a glass plate or a stainless steel plate, dry it at 60°C for 5 hours under infrared light to form a film, and then vacuum dry it at 80°C for 5 hours to obtain a proton exchange membrane sample 5 with a thickness of 50 μm.

[0063] Example 6

[0064] Step 1: Dissolve 1-(3,5-bis(trifluoromethyl)phenyl)-2,2,2-trifluoroethanone (31g, 0.1mol), m-terphenyl (11.5g, 0.05mol), and p-biphenyl (11.5g, 0.05mol) in 60ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6ml, 0.9mol). After the dropwise addition, polymerize for 12h in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it repeatedly with deionized water several times, and then vacuum dry it at 80°C for 12h to obtain an intermediate polymer.

[0065] Step 2: Add the above intermediate polymer (1.4 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise to react for 36 h. After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water, washed once with DCM and filtered to obtain the target sulfonated polymer. The synthesis equation is as follows:

[0066]

[0067] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying the obtained polymer at 80°C for 24 hours, dissolve it in a polar solvent DMF and centrifuge it, cast it on a glass plate or a stainless steel plate, dry it at 60°C for 5 hours under infrared light to form a film, and then vacuum dry it at 80°C for 5 hours to obtain a proton exchange membrane sample 6 with a thickness of 50 μm.

[0068] Example 7

[0069] Step 1: Dissolve 2,2,2-trifluoro-1-(pyridin-4-yl)ethan-1-one (17.5 g, 0.1 mol), p-terphenyl (11.5 g, 0.05 mol), and biphenyl (7.8 g, 0.05 mol) in 60 ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 ml, 0.9 mol). After the dropwise addition, polymerize for 12 hours in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it several times with deionized water, and then dry it in a vacuum at 80°C for 12 hours to obtain an intermediate polymer.

[0070] Step 2: Add the above intermediate polymer (1.2 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise, and react under this condition for 7 days (Note: the key is anhydrous reaction). After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water to finally obtain the target sulfonated polymer. The synthesis equation is as follows:

[0071]

[0072] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying the obtained polymer at 80°C for 24 hours, dissolve it in a polar solvent (one or more of NMP, DMF, DMSO, DMAc, etc.) and centrifuge it, cast it on a glass plate or a stainless steel plate, dry it at 60°C under infrared for 5 hours to form a film, and then vacuum dry it at 80°C for 5 hours to obtain a proton exchange membrane sample 7 with a thickness of 50 μm.

[0073] Example 8

[0074] 1) Representative structure 8 was synthesized according to Example 1.

[0075] Step 1: Dissolve 2,2,2-trifluoro-1-(pyridin-4-yl)ethanone (17.51 ​​g, 0.1 mol), m-terphenyl (11.5 g, 0.05 mol), and biphenyl (7.8 g, 0.05 mol) in 60 ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 ml, 0.9 mol). After the dropwise addition, polymerize for 12 hours in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it several times with deionized water, and then vacuum dry it at 80°C for 12 hours to obtain an intermediate polymer.

[0076] 2) Step 2: Add the above intermediate polymer (1.2 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise to react for 48 h. After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water to obtain the target sulfonated polymer. The synthesis equation is as follows:

[0077]

[0078] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying the obtained polymer at 80°C for 24 hours, dissolve it in a polar solvent DMSO and centrifuge it, cast it on a glass plate or a stainless steel plate, dry it at 60°C for 5 hours under infrared light to form a film, and then vacuum dry it at 80°C for 5 hours to obtain a proton exchange membrane sample 8 with a thickness of 50 μm.

[0079] Example 9

[0080] Step 1: Dissolve 2,2,2-trifluoro-1-(pyridin-4-yl)ethan-1-one (17.5 g, 0.1 mol), p-terphenyl (11.5 g, 0.05 mol), and biphenyl (11.5 g, 0.05 mol) in 60 ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 ml, 0.9 mol). After the dropwise addition, polymerize for 12 hours in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it several times with deionized water, and then vacuum dry it at 80°C for 12 hours to obtain an intermediate polymer.

[0081] Step 2: Add the above intermediate polymer (1.25 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform and stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise, and react under this condition for 7 days (Note: the key is anhydrous reaction). After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water to finally obtain the target sulfonated polymer. The synthesis equation is as follows:

[0082]

[0083] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying the obtained polymer at 80°C for 24 hours, dissolve it in a polar solvent DMAc and centrifuge it, cast it on a glass plate or a stainless steel plate, dry it at 60°C under infrared for 5 hours to form a film, and then vacuum dry it at 80°C for 5 hours to obtain a proton exchange membrane sample 9 with a thickness of 50 μm.

[0084] Example 10

[0085] Step 1: Dissolve trifluorobutanone (6.3 g, 0.05 mol), 1-(3,5-bis(trifluoromethyl)phenyl)-2,2,2-trifluoroethanone (16.5 g, 0.05 mol), and biphenyl (15.6 g, 0.1 mol) in 60 ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 ml, 0.9 mol). After the dropwise addition, polymerize for 12 h in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it repeatedly with deionized water several times, and then vacuum dry it at 80°C for 12 h to obtain an intermediate polymer.

[0086] Step 2: Add the above intermediate polymer (0.9 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise to react for 36 h. After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water, washed once with DCM and filtered to obtain the target sulfonated polymer. The synthesis equation is as follows:

[0087]

[0088] Step 3: The sulfonated polymer is washed with distilled water and filtered to obtain a light yellow powdery polymer. The obtained polymer is vacuum dried at 80°C for 24 hours, dissolved in a polar solvent DMF and centrifuged, cast on a glass plate or a stainless steel plate, and dried at 60°C for 5 hours under infrared conditions to form a film. The film is then vacuum dried at 80°C for 5 hours to obtain a proton exchange membrane sample 10 with a thickness of 50 μm.

[0089] Embodiment 11

[0090] Step 1: Dissolve trifluorobutanone (6.3 g, 0.05 mol), 1-(3,5-bis(trifluoromethyl)phenyl)-2,2,2-trifluoroethanone (16.5 g, 0.05 mol), and p-biphenyl (23 g, 0.1 mol) in 60 ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 ml, 0.9 mol). After the dropwise addition, polymerize for 12 h in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it repeatedly with deionized water several times, and then vacuum dry it at 80°C for 12 h to obtain an intermediate polymer.

[0091] Step 2: Add the above intermediate polymer (0.9 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise to react for 72 h. After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water, washed once with DCM and filtered to obtain the target sulfonated polymer. The synthesis equation is as follows:

[0092]

[0093] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying the obtained polymer at 80°C for 24 hours, dissolve it in a polar solvent DMAc and centrifuge it, cast it on a glass plate or a stainless steel plate, dry it at 60°C under infrared for 5 hours to form a film, and then vacuum dry it at 80°C for 5 hours to obtain a proton exchange membrane sample 11 with a thickness of 50 μm.

[0094] Example 12

[0095] Step 1: Dissolve trifluorobutanone (6.3g, 0.05mol), 1-(3,5-bis(trifluoromethyl)phenyl)-2,2,2-trifluoroethanone (16.5g, 0.05mol), and m-biphenyl (23g, 0.1mol) in 60ml DCM, cool to 0°C with an ice bath, and drop TFSA (79.6ml, 0.9mol). After the dropwise addition, polymerize for 12h in an ice bath. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it repeatedly with deionized water several times, and then vacuum dry it at 80°C for 12h to obtain an intermediate polymer.

[0096] Step 2: Add the above intermediate polymer (0.9 g, 3.000 mmol) to a flask and pass argon gas into it for 30 min. Add 50 mL of anhydrous chloroform to stir the polymer until it dissolves, then add 4.2 mL (27.264 mmol) of trimethylsilyl chlorosulfonic acid dropwise to react for 36 h. After the reaction is completed, the mixture is evaporated to remove excess solvent. The resulting solid is dissolved in DMAc and poured into an aqueous solution of 0.05 M NaOH. The precipitated solid is washed three times with deionized water, washed once with DCM and filtered to obtain the target sulfonated polymer. The synthesis equation is as follows:

[0097]

[0098] Step 3: Wash the sulfonated polymer with distilled water and filter to obtain a light yellow powdery polymer. After vacuum drying at 80°C for 24 hours, dissolve in a polar solvent DMF and centrifuge, cast on a glass plate or a stainless steel plate, and dry at 60°C for 5 hours under infrared conditions to form a film. Then, vacuum dry at 80°C for 5 hours to obtain a proton exchange membrane sample 12 with a thickness of 50 μm.

[0099] The ion exchange capacity (IEC) of proton exchange membrane samples 1 to 12 was measured according to the method for determining ion exchange capacity of proton exchange membrane GB / T20042.3-2022: the pre-dried membrane was weighed (W membrane), soaked in 25 mL of 2M NaCl solution for 24 h, then the membrane was taken out of the solution and titrated to neutral pH with 0.01 M NaOH standard solution, using phenolic acid as an indicator. The consumption of NaOH was recorded as V NaOHTitrate three times and take the average value, and calculate it using formula (1) as follows:

[0100] IEC=0.01*V NaOH / W 膜 (1);

[0101] The measurement results are shown in Table 1.

[0102] Table 1

[0103]

[0104] Since a large number of proton exchange membrane samples were prepared in the above embodiment, for ease of measurement, the water absorption and ion conductivity of proton exchange membrane sample 2, proton exchange membrane sample 5, and proton exchange membrane sample 8 at 25°C and 80°C were measured with reference to the water absorption and ion conductivity determination method of proton exchange membrane GB / T20042.3-2022. The test results are shown in Table 2.

[0105] Table 2

[0106]

[0107] In addition, the proton exchange membrane sample 5 was taken and its mechanical properties were measured according to the mechanical properties test method of proton exchange membrane GB / T 20042.3-2022; the test results are as follows: Figure 1 As shown by Figure 1 It can be seen that the proton exchange membrane sample 5 has a tensile strength of at least 35 MPa. At the same time, the elongation at break is tested to show that the proton exchange membrane sample 5 has improved flexibility by introducing a long alkane side chain, and has an elongation at break of more than 50%.

[0108] The glass transition temperature (Tg) was measured by differential scanning calorimetry (DSC) using a TA instrument Q20, with a scanning temperature of 20 to 300°C and a heating rate of 10°C / min. Proton exchange membrane sample 5 had a higher Tg (glass transition temperature) of 100 to 150°C, and the Tg of the perfluorosulfonic acid proton membrane was about 90°C.

[0109] Chemical stability test: PEM sample 2, PEM sample 5, and PEM sample 8 were subjected to Fenton reagent (2ppm Fe 2+ / 3% H2O2) for 1 hour, and then the free radical degradation weight loss was tested. The results are as follows Figure 4 As shown by Figure 4 It can be seen that the degradation of proton exchange membrane sample 2 is stable (the weight loss of free radical degradation is only 3.69%); under the same conditions, the weight loss of polymer sample 5 is only 3.57%, and the weight loss of polymer sample 8 is only 4.12%, indicating that the above-mentioned proton exchange membrane polymer has high chemical stability.

[0110] When the proton exchange membrane sample 5 is used as the proton exchange membrane of a proton exchange water electrolyzer, the current density is at least 1.5 A cm at a voltage of 1.8 V. -2 The Pt / C and Ir catalysts on the cathode and anode of the electrolytic cell are 0.5 mg cm -2 , 1.0mgcm -2 The test conditions are that the electrolytic cell temperature and water temperature are 60°C. The test results are as follows Figure 2 , Figure 3 As shown, when the polymer was tested in the electrolytic cell for 300 hours, there was basically no attenuation. According to the above test results, the stability of the proton exchange membrane sample 5 has been significantly improved.

[0111] In summary, the proton exchange membrane prepared by the present invention has high IEC, high chemical stability, low water absorption and swelling rate, and high mechanical strength, and can be used as an electrolyte for proton exchange membrane fuel cells.

[0112] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a block all-carbon-carbon connected proton exchange membrane, characterized in that: The following steps are involved: S1. Dissolve 31 g of 1-(3,5-bis(trifluoromethyl)phenyl)-2,2,2-trifluoroethanone, 11.5 g of m-terphenyl, and 7.8 g of biphenyl in 60 mL of DCM, cool to 0°C with an ice bath, add 79.6 mL of TFSA dropwise, and polymerize for 12 h under ice bath conditions after the addition is complete; after the reaction is complete, add DMSO to quench and dissolve the polymer, sink it into ice water to obtain a white solid, rinse it repeatedly with deionized water several times, and then vacuum dry it at 80°C for 12 h to obtain an intermediate polymer; S2, add 1.2g of the intermediate polymer into a flask, and pass argon gas into it for 30 min; add 50mL of anhydrous chloroform to stir the polymer until it dissolves, and then add 4.2mL of trimethylsilyl chlorosulfonic acid dropwise to react for 12h; after the reaction is completed, the mixture is evaporated to remove excess solvent; the obtained solid is dissolved in DMAc, and poured into a 0.05M aqueous solution of NaOH, the precipitated solid is washed three times with deionized water, washed once with DCM and filtered to obtain the target sulfonated polymer; S3. The sulfonated polymer is washed with distilled water and filtered to obtain a light yellow powdery polymer. The obtained polymer is vacuum dried at 80°C for 24 hours, dissolved in a polar solvent NMP and centrifuged, cast on a substrate, and dried at 60°C for 5 hours under infrared conditions to form a film. The film is then vacuum dried at 80°C for 5 hours to obtain a proton exchange membrane with a thickness of 50 μm.

2. The method for preparing a block all-carbon-carbon connected proton exchange membrane according to claim 1, characterized in that: The substrate is one of a stainless steel plate, a glass plate, a PET plate, a polypropylene plate and a polyester film.

3. A block all-carbon-carbon-connected proton exchange membrane prepared by the method according to claim 1 or 2.

4. Use of the segmented all-carbon-carbon-connected proton exchange membrane as claimed in claim 3 in the preparation of a proton exchange membrane fuel cell.

Citation Information

Patent Citations

  • Proton exchange membrane

    CN115477778A

  • Proton Exchange Membrane

    CN115490899B

  • Sulfonated phenylene polymer as well as preparation method and application thereof

    CN116813853A